2014
DOI: 10.1007/s11033-014-3677-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NAT2 in immune system cells and the relation of NAT2 gene polymorphisms in the anti-tuberculosis therapy in Mexican mestizo population

Abstract: Arylamine N-acetyltransferase 2 (NAT2) metabolizes isoniazid (INH) and Single Nucleotide Polymorphisms (SNP) responsible for its activity has been reported. The aim of this study in the Mexican mestizo population was to evaluate NAT2 expression at the protein level in immune cells, as well as the distribution and frequency of six NAT2 SNPs and their association with anti-TB therapy, by measuring the plasma levels of INH and Acetyl-INH (AcINH). We performed genotyping assays of NAT2 SNPs in 40 TB patients and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
5
8
0
1
Order By: Relevance
“…It has been reported that 52%‐72% of Caucasians have slow acetylating phenotypes, while 34%‐61% of Africans carry slow acetylated phenotypes . In America, the rate of slow acetylation types ranges from 23% to 75%, while Asians only have 9%‐32% of the slow acetylation phenotype . In this study, we found that slow acetylation in Mongolian tuberculosis patients accounted for 29.4%, which was consistent with Asians.…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that 52%‐72% of Caucasians have slow acetylating phenotypes, while 34%‐61% of Africans carry slow acetylated phenotypes . In America, the rate of slow acetylation types ranges from 23% to 75%, while Asians only have 9%‐32% of the slow acetylation phenotype . In this study, we found that slow acetylation in Mongolian tuberculosis patients accounted for 29.4%, which was consistent with Asians.…”
Section: Discussionsupporting
confidence: 80%
“…The presence of slow acetylation activity SNPs has been linked to the risk of developing type 2 diabetes [7, 8]. The sample of healthy volunteers participating on this study showed a high prevalence of a slow acetylation phenotype consistent with previous reports with larger samples of Mexican [34, 37] and Central American populations [43]. This can be attributed to the admixture effect present on American mestizo groups [44, 45].…”
Section: Discussionsupporting
confidence: 86%
“…Six SNPs were analyzed: rs1041983 (282C>T), rs1801280 (341T>C), rs1799929 (481C>T), rs1799930 (590G>A), rs1208 (803A>G) and rs1799931 (857G>A). The genotyping assays were performed as previously described [34]. Briefly, A 20X primer and probe mix was supplied for each assay, and a 1X concentration of this mix as well as a half volume of 2X TaqMan® Genotyping Master Mix (Life Technologies, Waltham, MA, USA) and 10 ng/μL of the genomic DNA sample were added to each well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otros países ya han reportado los genotipos de NAT2 en sus poblaciones, entre ellos están, China (28) , México (28)(29)(30) , Morocco (31) , India (32) y Brasil (33) , encontrado diferencias en sus genotipos comparados con los de otras poblaciones. La Tabla 2a muestra un metaanálisis de las frecuencias de los alelos de NAT2 en nueve poblaciones (31) .…”
Section: Nat2unclassified